Vloga moških oblačil v jaromeščanskem ambientu Kersnikovih romanov Ciklamen in Agitator - Perović, Ana (Slavia Centralis, 2020)
THE ROLE OF MEN’S CLOTHING IN THE FAUX-BOURGEOIS AMBIENCE OF KERSNIK’S NOVELS CIKLAMEN AND AGITATOR In this paper we consider men’s clothing designs as they are depicted in Kersnik’s novels Ciklamen and Agitator. We analyse them as part of the Slovene petit bourgeois ambience. As such, the clothes serve the function of portraying the relative underdevelopment of Slovene provinces in the second part of the 19th century. The interclass and intraclass differentiation indicated through clothing is used in a comical function and different clothing designs suggest personality features of individuals.